2020
DOI: 10.1177/0020872819896849
|View full text |Cite
|
Sign up to set email alerts
|

The capability approach in social work research: A scoping review of research addressing practical social work

Abstract: This study reports the findings from a scoping review of the use of the capability approach in social work research. We identified 17 peer-reviewed journal articles which actively used the capability approach and addressed social work practice. The purpose was to examine how the use of the capability approach was linked to policies, practices and social justice approaches in social work research. The merits and challenges of the capability approach in social work research are discussed. Four main applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…It too references some iconic bodies of conceptual thinking, notable for their breadth and intellectual pedigrees rather than their ease of translation into concrete operational guidelines. This is evidenced in rejection of an adverse substituted judgment form of paternalism, pursuit of personal empowerment, and resonance with writing on capability theory and capacity-building (in law and social work: Kjellberg andJansson 2020, Carney 2017). But no international treaty, domestic law or program achieves its old or new purpose merely by virtue of writing it down.…”
Section: A Slippery Conceptual Landscapementioning
confidence: 99%
“…It too references some iconic bodies of conceptual thinking, notable for their breadth and intellectual pedigrees rather than their ease of translation into concrete operational guidelines. This is evidenced in rejection of an adverse substituted judgment form of paternalism, pursuit of personal empowerment, and resonance with writing on capability theory and capacity-building (in law and social work: Kjellberg andJansson 2020, Carney 2017). But no international treaty, domestic law or program achieves its old or new purpose merely by virtue of writing it down.…”
Section: A Slippery Conceptual Landscapementioning
confidence: 99%
“…Research findings relevant to social work professionals and researchers can be found in many journals from different disciplines. In order to understand how the capability approach has actually been used in social work research, a scoping review was conducted (Kjellberg & Jansson, 2020). A scoping review shares some similarities with systematic reviews, such as the use of rigorous and transparent methods to identify and analyse relevant literature regarding a well-defined topic.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…The focus of the review was to identify and analyse how the capability approach is used in social work research, including research employing a range of different methods, and not to critically evaluate the research for best practice, as would have been the focus in a systematic review. After a two-step screening, 17 articles were included in the analysis (Kjellberg & Jansson, 2020). Only three of these articles addressed social work with older people (Horrell et al, 2015;Tanner et al, 2018;Yeung & Breheny, 2016).…”
Section: Methodological Frameworkmentioning
confidence: 99%
See 2 more Smart Citations